Contemporary Management of Proximal Humeral Fractures - Stockwell, Erin; Ahmed, Adil; Mir, Hassan R (Journal of the American Academy of Orthopaedic Surgeons, 2025)
Proximal humerus fractures (PHFs) are common injuries managed by orthopaedic surgeons. Treatment for PHFs remains somewhat controversial. This review article discusses indications, techniques, and outcomes for several modes of contemporary management of PHFs including nonsurgical treatment, surgical fixation, and reverse shoulder arthroplasty.